2014
DOI: 10.1002/jso.23624
|View full text |Cite
|
Sign up to set email alerts
|

Primary pulmonary classical Hodgkin lymphoma: A case report

Abstract: Primary pulmonary Hodgkin lymphoma (PPHL) is a rare entity. Most reported cases occurred before the availability of PET scan for accurate staging of the disease. We report a case of PPHL for which PET/CT scan was used and surgery was performed to confirm the diagnosis. A review of cases of PPHL since 1990 suggests that adjuvant chemotherapy and/or radiation therapy after surgical resection of the lung lesions achieve better disease control than surgical resection alone. J. Surg. Oncol. 2014 110:341–344. © 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Surgery has been mostly performed in the setting of an uncertain diagnosis. In those cases, it has been suggested that adjuvant chemotherapy and/or postoperative radiation therapy is associated with better disease control than surgery alone [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery has been mostly performed in the setting of an uncertain diagnosis. In those cases, it has been suggested that adjuvant chemotherapy and/or postoperative radiation therapy is associated with better disease control than surgery alone [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPHL is a rare visceral Hodgkin disease, comprised of 1.5%–2.4% of primary pulmonary lymphomas, which shows a slight female preponderance (F: M = 1.4: 1) and bimodal age distribution (<35 and >60 years) 3,4 . Clinically, most of the PPHL patients present with unspecific respiratory symptoms, such as cough, hemoptysis, chest pain, and dyspnea, whereas others can also manifest as fever, night sweats, weight loss, or be asymptomatic 5 . Intermittent fever and arthralgia as the predominant symptom of PPHL are quite rare.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Clinically, most of the PPHL patients present with unspecific respiratory symptoms, such as cough, hemoptysis, chest pain, and dyspnea, whereas others can also manifest as fever, night sweats, weight loss, or be asymptomatic. 5 Intermittent fever and arthralgia as the predominant symptom of PPHL are quite rare. When suggestive features such as lymphadenopathy and hepatosplenomegaly are absent at the initial time, these patients may be misdiagnosed with rheumatoid arthritis as in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…2 The commonest variety of this disease is the nodular sclerosis variant that comprises about 70% of PPHL. 3 PPHL affects women more frequently than men. 1 …”
Section: Discussionmentioning
confidence: 99%
“…2 The commonest variety of this disease is the nodular sclerosis variant that comprises about 70% of PPHL. 3 PPHL affects women more frequently than men. 1 Clinical features of the disease are usually nonspecific, presenting mainly as difficulty in breathing, night sweat, long-standing cough with generalized weakness, and weight loss.…”
Section: Discussionmentioning
confidence: 99%